Unusual hard palate swelling in an infant: A case of impacted pistachio shell - Shruthi, Muppidi; Kantala, Santhosh Reddy; Mandali, Satish; Burli, Pradeep (Indian Journal of Case Reports, 2024)
Children are prone to foreign body aspiration. Impaction of foreign bodies in the hard palate is a rare phenomenon. We present a case report where the infant’s palatal swelling was mistaken for a tumor or cyst and was planned for excision and later turned out to be an impacted pistachio shell. We emphasize considering the foreign body as a differential diagnosis in children who present with unusual hard palate mass.